Dr. Jung at the Site of Blood: A Note on Blown Figures - Stape, John H. (Studies in Canadian Literature, 1977)
Clues to the identity of Audrey Thomas's Miss Miller of Blown Figures can be found in Jung's account of his analytical work with a young American woman, known by the pseudonym of Frank Miller, who formed the basis for Thomas's character. In a 1975 interview, Thomas herself acknowledges the importance of Jung. The two Miller women meet similar ends not only as victims of the real world, but also as prey to the demons of their own inner worlds.